How to Read Karl Barth’s Church Dogmatics in One Book: A Sequential Guide to His Magnum Opus: Oleh Daniel Chitrada - Aulia Simon Partogi Situmeang (Indonesian Journal of Theology, 2026)
A book review of How to Read Karl Barth’s Church Dogmatics in One Book: A Sequential Guide to His Magnum Opus,